Faktor Ibu dalam Pemberian Makanan Pendamping ASI Secara Dini di Puskesmas Bajeng Kabupaten Gowa - Nurnainah, Nurnainah; Nurnaeni, Nurnaeni; Ismail, Ismail (Yayasan Mandar Indonesia, 2024)
Knowledge occurs after a person makes an infiltration of a particular object. The transmission of objects occurs through the human senses of sight, hearing, smell, taste and rejection by itself. Attitude is a level of affection, both positive and negative in relation to psychological objects, such as: symbols, phrases, slogans, people, institutions, ideals and ideas. The aim of this study is to find out the facts that influence mothers in the early delivery of accompanying food in Puskesmas Bajeng District of Gowa. The study was carried out in Puskesmas Bajeng District of gowa with a sample of 35 mothers. This study aims to determine the knowledge and attitudes of mothers with early breastfeeding to infants and identify the influence of these variables and with analytical descriptive research methods and crossectional approaches. There is an influence between mother's knowledge of giving early breastfeeding in Puskesmas Bajeng district of Gowa based on the statistical test Chi-Square obtained a value p=0,003 < α=0,05. The conclusion of this study is that the knowledge and attitude of the mother is related to the early delivery of accompanying food in the Puskesmas Bajeng district of Gowa.